Seaport Continuity Modelling Toward Pandemic Disaster Preparedness in the Future - Keng Bin Loke; Lai Fatt Chuah; Mohd Saiful Izwaan Saadon; Norlinda Mohd Rozar; Zhang Qiang; Mohd Tahir Mohd Azis; Nurul Hani Amirah Rahim; Anuar Abu Bakar; Mokhtar Kasypi; Mohd Azhafiz Abdullah (Chemical Engineering Transactions)
A seaport is an important economic and logistics node for any country. It provides opportunities for country development, deepening regional cooperation and promoting prosperity in the global supply chain. Seaports around the world are facing difficulty, congestion and delays, especially during the Covid-19 pandemic. Not only that, thousands of seafarers were also stranded at sea due to restrictions and prevention purposes, as well as seaports facing shortages of manpower, equipment and containers. The resulting supply chain bottlenecks hampered economic recovery. While the pandemic seems to be over, it may come again, new deadly germs may appear in the future. European researchers have isolated 13 new viruses from seven different ancient Siberian permafrost samples. Their study highlighted climate change melting the permafrost which revived a host of zombie and contagious viruses. Seaports should gradually shift to a “just in case” supply chain model and establish seaport continuity modelling to ensure sustainability and practicability of the operating system for future outbreaks. Survey activity and Analytic Hierarchy Process (AHP) analysis are used to determine the priority criteria of seaport continuity modelling and then a modelling is established based on the findings results. Initial results show that port efficiency (0.4352), port digitalization (0.3435) and port resilience (0.2213) are the main criteria for the establishing of the modelling. While port community system (0.1486) is the first sub-criterion, marine operation, terminal operation and hinterland operation (0.1451) are the second sub-criterion, artificial intelligence (0.1160) is the third sub-criterion, among others. The establishment of seaport continuity modelling can minimize the negative impacts for future pandemics and strengthen seaport capabilities in times of uncertainty.